Assessment of the purpose of South Africa's controlled foreign company rules - Holliday, Terry-Sue (Department of Finance and Tax, 2021)
Controlled foreign company (CFC) rules are anti-avoidance provisions designed to deter taxpayers from shifting their capital (and resultant income) to low-tax jurisdictions. Adoption of these rules in South Africa coincided with the relaxation of exchange control laws which opened up borders to inward and outward capital flows. South Africa's CFC regime has been amended over the years to become one of the most sophisticated amongst the G20 and aligned with the Organisation for Economic Co-operation and Development's (OECD) Action 3 recommendations (per the OECD's Base Erosion and Profit Shifting Action Project). Abusive profit-shifting tactics committed by multinational enterprises (MNEs) have caused the OECD to recommend that CFC rules be strengthened globally to combat this behaviour. However, in the United States and the United Kingdom, recent reforms appear to have weakened these countries' CFC (or CFC-equivalent) legislation, countering the OECD's recommendations. Such manoeuvres improve the profitability of these nations' MNEs by allowing their tax bills to remain lower than their international competitors'. As such, there is a danger of starting a race to the corporate tax-rate bottom where developing nations will be the losers, considering their greater reliance on corporate tax revenues than their developed counterparts. India and Brazil, both developing nations and BRICS members like South Africa, also aren't prioritising the strengthening of their CFC regulations – their focus is rather on improving transfer pricing (TP) legislation and enforcement to combat the damaging effects MNEs' avoidance practices are having on tax revenue collections in those countries. The existence of South Africa's advanced CFC legislation amongst a global trend of a weakening in, or the non-adoption of, CFC rules may hinder the competitiveness of South African MNEs. The current CFC regime could thus serve the purpose of stifling growth and foreign direct investment, instead of only deterring profitshifting behaviour. TP legislation targeted at MNEs (the biggest profit-shifting culprits) may yield the most effective anti-avoidance results. South Africa's recently enhanced TP reporting requirements are key to solving the offshore profit-shifting puzzle, as these reports will reveal information about an MNE's global operations and resultant profit-shifting activities. In addition, the revision to the TP arm's length principle to align compensation and value creation, will see profit-shifting MNEs bear the tax they were trying to avoid. It appears that the anti-avoidance purpose embodied within CFC regulations overlaps with the anti-avoidance mechanisms that these enhanced TP rules are designed to achieve. Thus, in a South African context, the most efficient way to curb tax avoidance may be to rely on TP, rather than CFC, legislation. As such, it is recommended that South Africa's CFC regulations be repealed.